Foreign corporate accountability: The contested institutionalization of mandatory due diligence in France and Germany - Maria-Therese Gustafsson; Almut Schilling-Vacaflor; Andrea Lenschow (Regulation & Governance, 2022)
In the recent past, European states have adopted mandatory due diligence (MDD) laws for holding companies accountable for the environmental and human rights impacts of their supply chains. The institutionalization of the international due diligence norm into domestic legislation has, however, been highly contested. Our contribution analyzes the discursive struggles about the meaning of due diligence that have accompanied the institutionalization of MDD in Germany and France. Based on document analysis and legal analysis of laws and law proposals, we identify a state-centric, a market-based, and a polycentric-governance discourse. These discourses are based on fundamentally different understandings of how the United Nations Guiding Principles on Business and Human Rights should be translated into hard law. By outlining these discourses and comparing the related policy preferences, we contribute with a better understanding of different ways in which MDD is institutionalized, with important consequences for the possibilities to enhance corporate accountability in global supply chains.
Keywords: 330; corporate accountability; discourse analysis; due diligence; public policy; supply chain